If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + c) = 2(c + -6) (1 * 3 + c * 3) = 2(c + -6) (3 + 3c) = 2(c + -6) Reorder the terms: 3 + 3c = 2(-6 + c) 3 + 3c = (-6 * 2 + c * 2) 3 + 3c = (-12 + 2c) Solving 3 + 3c = -12 + 2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2c' to each side of the equation. 3 + 3c + -2c = -12 + 2c + -2c Combine like terms: 3c + -2c = 1c 3 + 1c = -12 + 2c + -2c Combine like terms: 2c + -2c = 0 3 + 1c = -12 + 0 3 + 1c = -12 Add '-3' to each side of the equation. 3 + -3 + 1c = -12 + -3 Combine like terms: 3 + -3 = 0 0 + 1c = -12 + -3 1c = -12 + -3 Combine like terms: -12 + -3 = -15 1c = -15 Divide each side by '1'. c = -15 Simplifying c = -15
| 6x-3=2x^2 | | 5-2n=3-n | | 5t-(2T+14)=3T-14 | | 3(-6)+6(-6)=3-9 | | 14+2(11-h)=-5 | | -2(4b+2)+(9b-4)=0 | | 4t^2-25t+6=0 | | 5(-x-5)=-30 | | -1550-7x=1718 | | 3(x+4)=5x+16 | | 6h-117=-21 | | 8(x+2)+1=4x+4(4+x) | | 3(5x+6)+5(3x+3)+3=30x+37 | | 8x-1=9x-5 | | 39(x+4)=5x+16 | | 5-2y=3x | | 118.8-7.7x=3.3+39.6 | | 8=-5y-2 | | 2/3-7= | | -5n+x=78 | | 8(2n-3)=(2n+8)+3 | | 5x+5x+4+8=7x+4+2x | | -3(t+4)=3 | | 3(2-z)*0.2=z | | (3x)+4=-11 | | 11(2+8x)-10(10-11x)=912 | | -2(x-18)=(-x/2+3)(-3) | | 12=4n-10 | | x^3=216 | | -5=-x+3 | | 6x+2+3x+17=10 | | 3n+6n=3-9 |